Analisis Yuridis Peran UU Otonomi Khusus Papua terhadap Efisiensi Keseimbangan dan Pembangunan Ekonomi di daerah Otonom - Maidir Riwanto; Parningotan Malau (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the role of Papua’s Special Autonomy Law in achieving efficiency and balance in regional economic development and to assess the extent to which the policy protects indigenous peoples’ rights from a juridical perspective. The background of this research lies in the fact that Special Autonomy for Papua was designed as an instrument of asymmetric decentralization to address development inequality, social marginalization, and the historical complexity of Papua. However, its implementation has revealed a significant gap between the normative objectives of the law and the realities in practice, particularly in relation to the distribution of development benefits, institutional effectiveness, indigenous participation, and the protection of customary land rights. This study employs a normative juridical method using statutory, conceptual, and case approaches, with qualitative analysis based on library research. The findings show that Papua’s Special Autonomy has a strategic normative position in accelerating economic development through fiscal support, regional authority, and infrastructure development. Nevertheless, its effectiveness remains suboptimal due to weak institutional capacity, limited inter-agency coordination, low transparency, and insufficient involvement of indigenous communities in the development process. In addition, a development orientation that prioritizes economic growth and political stability often neglects the social, cultural, and constitutional rights of indigenous peoples. This condition has generated inequality, social conflict, and injustice in the management of natural resources. Therefore, it can be concluded that the success of Papua’s Special Autonomy is determined not only by the scale of authority and funding provided, but also by regulatory harmonization, institutional strengthening, respect for indigenous rights, and the implementation of inclusive, participatory, just, and sustainable development policies.